2008
DOI: 10.1177/0270467607313953
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Rural District Heating by Bio-Steam Supplied by a Paper Mill in Canada

Abstract: The feasibility of implementing district heating in a small town adjacent to a kraft pulp mill in Eastern Canada has been investigated. A detailed heat demand analysis was performed for all buildings using a Geographical Information System and archived data provided by the municipality. It was first shown that the total space heating requirement of the town could be supplied by exportable steam produced by the mill from forest biomass even during exceptional peak demands. However a screening test based on load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The local conditions used in the scenario are summarized in Table 8. (Fröling et al 2004) Energy losses in district heating pipelines 8.6% (Marinova et al 2008) Ce 0.1142 $/kWh (Hydro-Quebec 2018)…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The local conditions used in the scenario are summarized in Table 8. (Fröling et al 2004) Energy losses in district heating pipelines 8.6% (Marinova et al 2008) Ce 0.1142 $/kWh (Hydro-Quebec 2018)…”
Section: Figurementioning
confidence: 99%
“…Grand Forks and Vancouver have similar ambient temperature, but Vancouver has almost 4 times larger population density than Grand Forks. Studies in the literature have reported that a district heating system may not be economically viable in regions with low population density (Marinova et al 2008). The DWHRS installed in Grand Forks has a payback period of 1 to 2 years, while the district heating system has a payback period of 17 to 18…”
Section: Comparing the Dwhrs With A Wwshp Used For District Heatingmentioning
confidence: 99%
“…th century, with one geothermal district heating system in continuous operation in France (Chaudes-Aigues thermal station) since that time [18]. The US Naval Academy constructed the first district system in USA on its Annapolis campus in 1853, and the commercial district heating system in New York was built in 1877 [19]. The first district energy system in Canada was built in Winnipeg's commercial core in 1924 [19].…”
Section: De Systems Have Been Used In Europe Since the 14mentioning
confidence: 99%
“…The US Naval Academy constructed the first district system in USA on its Annapolis campus in 1853, and the commercial district heating system in New York was built in 1877 [19]. The first district energy system in Canada was built in Winnipeg's commercial core in 1924 [19]. Northern European countries are the main users of district energy systems.…”
Section: De Systems Have Been Used In Europe Since the 14mentioning
confidence: 99%
“…DE systems can use fossil fuel, renewable energy and waste heat as energy sources, and facilitate intelligent integration of energy systems. DE systems offer many advantages for society [1]. DE technology and its potential enhancement have been described from different aspects [2].…”
Section: Introductionmentioning
confidence: 99%